Le mythe d'un leadership nigérian dans les relations inter-africaines - Nwokedi, Emeka (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
Nigeria's leadership role in inter-African relations remains a myth despite the country's assertiveness in the areas of liberation, conflict mediation and regional economic integration. Rhetoric and posturing in inter-African diplomacy have become a substitute for reality. Furthermore, the weakness of the Nigerian domestic structure and the effects of the structural adjustment programme negate Nigerians capabilities to exert a leadership in inter-African diplomacy.